1993
DOI: 10.1016/0092-8674(93)90530-4
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of the heterochronic gene lin-14 by lin-4 mediates temporal pattern formation in C. elegans

Abstract: During C. elegans development, the temporal pattern of many cell lineages is specified by graded activity of the heterochronic gene Lin-14. Here we demonstrate that a temporal gradient in Lin-14 protein is generated posttranscriptionally by multiple elements in the lin-14 3'UTR that are regulated by the heterochronic gene Lin-4. The lin-14 3'UTR is both necessary and sufficient to confer lin-4-mediated posttranscriptional temporal regulation. The function of the lin-14 3'UTR is conserved between C. elegans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
2,514
3
73

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,699 publications
(2,608 citation statements)
references
References 25 publications
18
2,514
3
73
Order By: Relevance
“…When Ambros, Ruvkun and colleagues reported the cloning and functional analysis of the first micro-RNA (miRNA), lin-4, in 1993, they also provided a glimpse of things to come on the mechanism of miRNA production (Lee et al, 1993;Wightman et al, 1993). The authors demonstrated that there existed two RNA species, the 22-nucleotide (nt) lin-4S and the less abundant, approximately 60 nt lin-4L.…”
mentioning
confidence: 99%
“…When Ambros, Ruvkun and colleagues reported the cloning and functional analysis of the first micro-RNA (miRNA), lin-4, in 1993, they also provided a glimpse of things to come on the mechanism of miRNA production (Lee et al, 1993;Wightman et al, 1993). The authors demonstrated that there existed two RNA species, the 22-nucleotide (nt) lin-4S and the less abundant, approximately 60 nt lin-4L.…”
mentioning
confidence: 99%
“…Les ARN non codants (ARNnc) qui en résultent sont vraisemblablement impliqués dans des méca-nismes sophistiqués et encore peu connus visant à réguler l'expression des gènes [3,4]. Le mode d'action d'un sous-type d'ARNnc, appelés microARN (miARN), a été l'un des premiers à avoir été mis à jour [5,6]. Ces petits ARN intracellulaires longs de 22 nucléotides sont capables d'induire l'extinction (silencing) de l'expression de gènes par des méca-nismes de régulations post-transcriptionnelles, en se fixant de manière ciblée aux parties 3' non traduites (3'UTR) des ARNm et en provoquant un blocage de la traduction ou la dégradation de ceux-ci (Figure 2) [7,8].…”
Section: Les Miarn Régulateurs Post-transcriptionnels De L'expressiounclassified
“…They act in trans ‐ upon cis ‐regulatory elements in target messenger RNAs, affecting protein translation (Lee et al, 1993; Wightman et al, 1993). MiRNAs are located in introns of other genes and intergenic regions of the genome.…”
Section: Introductionmentioning
confidence: 99%